Perawatan Pada Mesin Injection Molding untuk Pembuatan Grip Rem Tangan di PT. XYZ - Alex Tambers Tamba; Oleh Oleh (Peneliti.net, 2022)
The machine always operates every day so it must be carried out maintenance and maintenance regularly. In this case, one method that can be used is the OEE (Overall Equipment Effectiveness) method which serves to determine the effectiveness of the use and utilization of machines, equipment, time and materials in an operating system. So that it can reduce defects caused by the machine. This research is devoted to the J 280 AD Injection engine which has the highest level of damage. OEE is a metric that focuses on how effectively a production operation is being executed. Results are expressed in a generalized form that allows comparisons between manufacturing units in different industries. From this research, data obtained from the value of availability is 96.85%, the value of performance efficiency is 96.80%, and the rate of product quality is 99.49%. Therefore, in the October 2020 period, it was concluded that the OEE value of the Injection Molding machine had an OEE standard above the average of 93.43%, which means the machine has very good performance in this period. This Injection Molding Machine is still in a productive state and is very feasible to use.